Educational Music and Sounds Through the Lens of Theodor Adorno and Immanuel Kant - Erico Jaya Saputra; Fransiska Fransiska; Laura Kristia Dina; Octa Maria Sihombing; Mussion Eric (Yayasan Adra Karima Hubbi, 2023)
Background research is based on the assumption that music is likened to mirrors, languages, sound reflections, rhythms, harmonies and melodies. Harmonization was later adopted by education, especially music education worldwide. Music's reflection through education would not be separated from the music education's foundation, which is called philosophy. Thus, researchers subsequently highlighted philosophical foundations of music itself upon encountering education globally. Moreover, research in Indonesia rarely examines philosophical impulses with music (which is connected to sound and voice). Systematically thinking, radical to the roots in search of wisdom on sound (which comes from the vibration of the universe) and sound (which comes from living beings) in music became the aim of this research. Qualitative research method used here is bibliographic research by looking for secondary sources of previous research to establish relationships between Immanuel Kant and Theodor Adorno's ideas. Both philosophers' thoughts on sound and voice are explored through previous research or authors have discussed them in quantitative studies. The authors discuss it through quantitative research. Results show that both sound and voice based on Kant and Adorno both lead to a diversity of expressions without needing a categorical supplement